ANALISIS PENGARUH NON PERFORMING FINANCING, FINANCING TO DEPOSIT RATIO, PENYISIHAN PENGHAPUSAN AKTIVA PRODUKTIF, DAN BIAYA PENDAPATAN OPERASIONAL TERHADAP PROFITABILITAS DI KLKMS BTM PEMALANG KC RANDUDONGKAL TAHUN 2019-2022 - Puspitasari, Saras Meilia; Wuriah, Diah; Suripto, Suripto; Prasetyo, Arif Hadi (Dinamika Akuntansi Keuangan dan Perbankan, 2023)
This research is entitled "Analysis Of The Effect Of Non Performing Financing, Financing to Deposit Ratio, Provision For Elimination of Earning Assets and Cost of Operating income Against Profitability At KLKMS BTM Pemalang KC Randudongkal in 2019-2022“. The purpose of the study was to determine and analyze the effect of Non Performing Financing (NPF), Financing To Deposit Ratio (FDR), Provision for Removal of Earning Assets (PPAP), Operating Costs and Operating Income (BOPO) on Profitability. This study uses a saturated sample using a sample of 48 data. The tests in this study were carried out using descriptive analysis methods, normality tests, multicollinearity, heteroscedasticity, autocorrelation, linearity, multiple regression analysis, t test, f test and coefficient of determination. The results of this study indicate that the NPF variable (X₁) affects profitability (Y) the value of thitung ˂ ttabel (-5.433 ˂ 2.01290). The FDR variable (X₂) affects Profitability (Y) with a thitung > ttabel (3.093 > 2.01290). PPAP variable (X₃) affects Profitability (Y) with a thitung ˂ ttabel (-2.847 ˂ 2.01290). BOPO variable (X₄) affects Profitability (Y) with a thitung ˂ ttabel (- 3.625 ˂ 2.01290). NPF (X₁), FDR (X₂), PPAP (X₃), BOPO (X₄) variables have a significant effect together or as a whole on Profitability (Y) with a value of Fhitung > F tabel (24.149 > 2.57) at LKMS Cooperative BTM Pemalang Randudongkal Branch Office in 2019-2022.